NURSING CARE FOR PATIENTS DIAGNOSED WITH MYOCARDIAL INFARCTION - da Silva Caetano , Belkise; Rolim de Oliveira, Rafaela; Caroline de Souza, Anne; Ruston de Oliveira, Thárcio (Health and Society, 2023)
Introduction: AMI is among the main causes of hospitalization and death. This condition is a cardiovascular disease caused by the interruption of blood flow to the heart, due to the formation of a clot. This process causes the death of cells in important regions of the heart, which can lead to death. Based on the above, this study is justified by its academic, scientific and social relevance, based on knowing the risks, pathophysiology and essential care for patients diagnosed with AMI. Nursing professionals are often the first professionals to come into contact with patients who have chest pain and are consequently diagnosed with AMI, with the principle of assisting in the recovery of the disease and reintroducing these patients into their daily lives. In this regard, it is essential to know what nursing care is for patients with Acute Myocardial Infarction. Objective: To demonstrate the nursing care provided to patients with Acute Myocardial Infarction. Methodology: This study is an integrative literature review, with a descriptive approach, being carried out through a survey of data in the scientific bases: LILACS; SCIELO and BDENF. Results and Discussion: The multidisciplinary team’s assistance is directly related to systematic monitoring care, administration of prescribed medications, guidance on rest, avoiding sudden movements, diet care, maintaining oxygenation, strict water control, hygiene care, and among others. others. With regard to complications caused by AMI, mitral valve regurgitation stands out, which is a condition resulting from blood reflux triggered by failure to close the mitral valve. Ventricular septal rupture after AMI also stands out as one of the complications, this clinical condition corresponds to lesions in the muscular wall or septum located in the lower portion of the heart. Conclusion: For patients with AMI, but these interventions are a joint effort of multidisciplinary professionals involved in promotion, prevention, intervention and support to reduce complications and prevent disease progression. most effective when avoided.